The AxBioTick study – immune gene expression signatures in human skin bitten by Borrelia-infected versus non-infected ticks - Nellie Carlströmer Berthén; Samuel Cronhjort; Marika Nordberg; Per-Eric Lindgren; Marie Larsson; Peter Wilhelmsson; Johanna Sjöwall (BMC Infectious Diseases, 2024)
Abstract Background Borrelia infection is caused by Borrelia burgdorferi sensu lato and transmitted by Ixodes ricinus ticks, a common tick-borne infection in Northern Europe. The establishment of Borrelia infection depends on transmission of the spirochetes, as well as the immune response generated in the skin after a bite. Here we aim to investigate the local immune response in the skin after a tick bite and assess the possible direct effects of Borrelia, by applying gene expression analysis of the immune response in skin exposed to Borrelia-infected and non-infected ticks, respectively. Methods Skin biopsies from the study participants were taken 7–10 days after the tick-bite. The ticks and skin biopsies were analysed by real-time PCR for Borrelia spp. and other tick-borne pathogens. Dermal transcriptome profiles derived from RNA sequencing with focus on immune system regulation were created. In addition, we performed enrichment analysis of dermal transcriptome profiles with focus on immune system regulation. Results Skin biopsies exposed to a Borrelia-positive tick induced an overall higher expression of immune-related genes. Cytokines involved in the regulation of T-cell and macrophage activation, pro-inflammatory regulators and Toll-like receptor 2, 3 and 7 involved in pathogen recognition were upregulated in skin exposed to Borrelia, although Borrelia DNA was not detected in the biopsies. Conclusion The evidence of upregulation of genes in Borrelia exposed skin suggests an influence on the immune system of ticks and spirochetes. Characterization of Borrelia-associated gene expression signatures in the skin could contribute to future diagnostics and increase our understanding of the development of various manifestations of Borrelia infection.